Are police cautions a soft option? Reoffending among juveniles cautioned or referred to court. Issue 3 (September 2019) - Wang, Jia J; Weatherburn, Don
During the 1990s, many jurisdictions introduced police cautions as an alternative to referral to court for juveniles committing comparatively minor offences. The policy was motivated by a concern that contact with the court system for such offenders might be criminogenic. In recent years, however, elected officials have criticised police cautions as a 'soft option' and this (in some jurisdictions at least) has led to a decline in their use. Past research has often failed to ensure that the comparison group for a police caution consists of children referred to court who could have received a police caution. The current study overcomes this problem and employs a rigorous set of procedures for minimising the risk of selection bias. Our results indicate that cautioning young offenders who have committed comparatively minor offences and who have not previously been referred to court results in a lower risk of reoffending than referral to court. We conclude that restrictions on the use of cautions in these circumstances could increase the risk of juvenile reoffending.